Responding to the COVID‐19 Crisis: Transformative Governance in Switzerland - Willi, Yasmine (Tijdschr Econ Soc Geogr, 2020)
In the ongoing coronavirus disease 2019 (COVID‐19) crisis, uncertain and experimental forms of governance have emerged. Administrative routines and established management techniques have dissolved amid emergency actions and management by the state of exception. We refer to these emerging governance forms as transformative governance. Discussing examples from Switzerland, we illustrate how policy responses to COVID‐19 reflect transformative governance. These examples raise four issues that characterize transformative governance research and practice: (i) the evidence base of policy‐making; (ii) the role of the state in transformative governance; (iii) the potential of experimental governance; and (iv) the paradigms driving policy change. Our study demonstrates that these issues imply different opportunities and risks of transformative governance, which we discuss in detail.